The nutritional transition and diet-related chronic diseases in Asia: implications for prevention - Popkin, Barry M.; Horton, Susan; Kim, Soowon (International Food Policy Research Institute, 2001)
The nutritional transition currently occurring in Asia is one facet of a more general demographic/nutritional/epidemiological transition that accompanies development and urbanization, marked by a shift away from relatively monotonous diets of varying nutritional quality toward an industrialized diet that is usually more varied, includes more preprocessed food, more food of animal origin, more added sugar and fat, and often more alcohol. This is accompanied by shift in the structure of occupations and leisure toward reduced physical activity, and leads to a rapid increase in the numbers of overweight and obese. The accompanying epidemiological transition is marked by a shift away from endemic deficiency and infectious diseases toward chronic diseases such as obesity, adult-onset diabetes, hypertension, stroke, hyperlipidaemia, coronary heart disease, and cancer. Obesity is now a major public health problem in Asia. Obesity is a problem of the urban poor as well as the rich, and the urban poor have the added predisposing factors associated with low birthweight. Costs of chronic disease are estimated for China and Sri Lanka. Diet-related chronic disease is projected to increase and dietary factors (principally overweight) will account for an increased share of chronic disease, and childhood factors will decline in significance. Few program and policy options to address these issues have been undertaken in Asia. Agricultural policy is important, and the relatively cheap availability of vegetable oil may have had dramatic (adverse) dietary effects in Asia. Price policy has considerable potential, in particular the pricing of oils. Promoting a traditional diet has been quite helpful in holding down fat intake and obesity in Korea. Health promotion efforts in Mauritius succeeded in reversing several adverse trends contributing to coronary heart disease. Thailand has successfully used mass media for other health promotion efforts and is moving to pilot schemes in the area of chronic disease. And Singapore has been the leader in the region in exercise promotion and weight control in schools.